2012
DOI: 10.1007/s12257-012-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

The production of bioflocculants by Bacillus licheniformis using molasses and its application in the sugarcane industry

Abstract: A bioflocculant produced by B. licheniformis was investigated with regard to a low-cost culture medium and its industrial application. Molasses replaced sucrose as the sole carbon source in bioflocculant fermentation. The optimum low-cost culture medium was determined to be composed of 20 g/L molasses, 0.4 g/L urea, 0.4 g/L NaCl, 0.2 g/L KH2PO4, 1.6 g/L K2HPO4, and 0.2 g/L MgSO4. The bioflocculant from B. licheniformis was then applied to treat sugarcane-neutralizing juice to remove colloids, suspended particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…Zhuang et al. ( reported that the abundance of carbohydrates, amino acids, and proteins confers molasses with excellent properties for use as a possible substrate for bacterial growth culture and bioflocculant production.…”
Section: Molasses As a Substratementioning
confidence: 99%
“…Zhuang et al. ( reported that the abundance of carbohydrates, amino acids, and proteins confers molasses with excellent properties for use as a possible substrate for bacterial growth culture and bioflocculant production.…”
Section: Molasses As a Substratementioning
confidence: 99%
“…3,[9][10][11] During drinking water treatment, flocculation precipitation is the main method used due to its low cost and established process. Many chemical flocculants, including polyaluminum chloride (PAC) and AS, are widely used for drinking water treatment because of their high flocculating performance and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it needs pretreatment before use because of its adverse effect on cell growth and metabolism . Acid treatment coupled with bioflocculation would be a simple and effective pretreatment method for removing fermentation inhibitors . The suspended colloid and ash contents could be significantly reduced in PAM‐treated molasses solution compared with the original liquor; which may lead to better cell growth and improved sugar utilization.…”
Section: Resultsmentioning
confidence: 99%
“…The cleaning liquid was mixed with the bioflocculant agent polyacrylamide (PAM) at a final concentration of 2 mg kg −1 liquid, lightly stirred for 3 min and then left to stand for 30 min at 50 °C. The supernatant was reserved for fermentation experiments . The amount of reducing sugar was assayed by the dinitrosalicylic acid (DNS) method …”
Section: Methodsmentioning
confidence: 99%